(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Among the various types of acute coronary syndrome, NSTEMI has the most aggravating clinical courses. More severely, the clinical course may present as cardiogenic shock which is associated with a high burden of morbidity and mortality. Identifying the predictors of NSTEMI and the associated frequency of cardiogenic shock is of great value for diagnosis, risk stratification, and management. Objectives: The intention is to assess the incidence of cardiogenic shock among patients presenting with non-ST elevation myocardial infarction (NSTEMI) and how this frequency is modified by age, sex, comorbidities, and specific clinical and biochemical factors. Study Design: A cross-sectional study. Place and duration of study. From 01 December 2024 to 31 May 2025 Cardiology Department Sandeman Provincial Hospital / Bolan Medical College / Hospital, Quetta. Methods: A cross-sectional study was undertaken within a cardiology unit involving a cohort of 100 NSTEMI patients. For each patient, variables including data on clinical history, laboratory results, systolic blood pressure, left ventricular ejection fraction, serum creatinine level, and the presence/absence of diabetes were obtained. The definition of cardiogenic shock was based on standard hemodynamic parameters. The data were analyzed using SPSS version 24.0, with a p-value of <0.05 considered statistically significant. Results: Among the cohort of 100 NSTEMI patients, the mean age was 58.4 years (SD 11.7 years) and the sample was composed of 62% males and 38% females. 12% of the patients presented with shock. The mean systolic blood pressure of patients with shock was 86.5 mmHg (SD 8.2 mmHg) which was significantly lower (p = 0.001) than the 118.4 mmHg (SD 12.6 mmHg) of the non-shock patients. The mean left ventricular ejection fraction (LVEF) was also lower in shock patients, 34.2% (SD 7.8 %) as opposed to 49.5% (SD 8.6%) in non-shock patients (p = 0.002).Shock was also significantly associated with diabetes mellitus (p = 0.041) and higher levels of creatinine (p = 0.03). Conclusion: Cardiogenic shock presents as a complication in a notable percentage of NSTEMI cases, particularly in older, male NSTEMI patients with diabetes and renal insufficiency. Weakness of the left ventricular ejection fraction and lower systolic blood pressure were strong predictors of shock. In NSTEMI patients with hemodynamic instability, identification of such patients and immediate intervention will be critical in improving outcomes and lowering mortality.